A Note on the Heritability of Pod Length and Number of Seeds per Pod in Cowpea, Vigna unguiculata s.sp. unguicalata (L) Walp - Ogunbodede, B. A.; Fatunla, T. (Faculty of Agriculture, University of Ife, 2015)
KR 91, (a short podded cowpea cultivar) was crossed to Paraquay No. 2, (a long podded cultivar), while Victor (a crowder) was crossed with B33 (a non-crowder) to study the inheritance of pod length and seed number respectively in the two crosses. The two parents, PI, P2, and the progenies F1, BC1, BC2 and F2 of each cross were evaluated at the University of Ife Teaching and Research Farm. Narrow sense heritability estimates of 72.1% and 36.8% were obtained for pod length and number of seeds per pod respectively. About seven and eight pairs of genes control pod length and number of seeds per pod respectively.